When the boss is blue: examining the effects of supervisors' negative emotions on subordinates' cognitive work engagement and family undermining. Issue 2 (3rd August 2020) - Chan, Xi Wen; Kalliath, Thomas; Cheng, David
Abstract : Purpose: Research has largely shown that supervisors' negative emotions lead to subordinates' negative emotions and detrimental work outcomes, but recent studies are showing that supervisor negative emotions may yield both negative and positive subordinate behaviours. Drawing on the work–home resources model, this research sought to unpack the interpersonal, cross-domain effects of supervisor negative emotions on subordinate cognitive work engagement and family undermining through subordinate perceived leader effectiveness and self-efficacy to manage work and life. Design/methodology/approach: To test the relationships, confirmatory factor analysis and structural equation modelling were conducted on time-lagged dyadic data collected from 372 supervisor–subordinate pairs. Findings: Results revealed that supervisor negative emotions led to higher levels of subordinate cognitive work engagement and family undermining. Research limitations/implications: Supervisor negative emotions had unintended consequences on subordinates' work and family outcomes – they enhanced subordinates' cognitive work engagement (positive work outcome) but also increased subordinates' family undermining (negative family outcome). Future studies could benefit from a diary study with a within-subject design since emotions are known to fluctuate in a day. Practical implications: This research provides supervisors with insights about the consequences of their negative emotions on their subordinates, calls upon organisations to provide cognitive regulation training, and encourages subordinates to develop self-efficacy in managing their work and life. Originality/value: This study is among the first to incorporate self-efficacy to manage work and life as a personal resource and subordinate family undermining as an outcome of supervisor negative emotions, which enhances understanding of the resource allocation and loss processes between supervisors and subordinates.